Cancer incidence and nuclear facilities in Ukraine: a community-based stydy - Bazyka, D.A.; Prysyazhnyuk, A.Ye.; Romanenko, A.Ye.; Fedorenko, Z.P.; Gudzenko, N.A.; Fuzik, M.M.; Khukhrianska, O.M.; Trotsyuk, N.K.; Gulak, L.O.; Goroch, Ye.L.; Sumkina, Ye.V. (Experimental Oncology, 2012)
The study goal was to investigate malignant tumors incidence in 5 Ukrainian cities with nuclear hazardous enterprises: extractive, processing enterprises of uranium ore (Zhovti Wody and Dniprodzerzhynsk of Dnipropetrovsk region) and nuclear power stations (Energodar of Zaporizhska region, Pivdennoukrainsk of Mykolayivska region, Netishyn of Khmelnytska region). Materials and methods: average annual population of the cities under study in 2003–2008 was 439 600 persons. Total and specific cancer incidence was investigated. Site specific incidence was analyzed for malignancies proved to be radiosensitive in previous studies: trachea, bronchus and lung, breast, kidney, thyroid cancer and leukemia. Data on cancer cases were received in National Cancer Registry of Ukraine (National Cancer Institute). There was used the data of the State Statistics Committee of Ukraine on the size of the studied population by gender — age groups. Standardized incidence ratio of cancer at a whole and for each of five specific forms of malignancies were calculated for the population of each city and group of cities depending on the nature of industrial activity. Results: During the observed period there were registered 9 381 cancer cases in inhabitants of Ukrainian cities with radiation hazardous facilities. There was stated that cancer incidence rate in population of 5 cities significantly exceeded national and regional levels. Among specific forms of malignancy there were observed excess of lung, trachea, bronchus, breast, kidney cancer and leukemia in population of extractive, processing uranium ore cities. No excess of thyroid cancer was identified. In cities with nuclear power station there were registered excess of kidney cancer. Conclusion: Results of the study suggest the necessity to explore the role of various factors in forming the identified cancer incidence features in the Ukrainian population living near the nuclear power facilities.